Exploring the experiences and perceptions of expert panels on the rise of out-of-wedlock pregnancies among adolescents and youths in Malaysia - Othman, Nur Shahira; Ma’rof, Aini Azeqa; Kamarudin, Mohd Shahrul (Human Resource Management Academic Research Society, 2023)
This study aims to identify factors and effects of out-of-wedlock pregnancies among teenagers and youth in Selangor, Malaysia. Using a qualitative case study, interviews, and document research, six informants were selected for expert panel perspectives. The findings highlight the environment, including individuals, families, the internet, and social media, as the most significant factor. These pregnancies bear significant long-term implications, causing social difficulties, governmental strains, and challenges for the child's future, spanning welfare, emotional stability, marriage, and their own offspring. Based on the findings, it is recommended to implement comprehensive sexual education in schools, emphasizing the potential long-term effects of out-of-wedlock pregnancies. By addressing the identified environmental factors and mitigating the potential effects, there is hope to reverse this trend and better support the individuals involved. However, it is clear that a multi-pronged approach involving educational institutions, parents, the online community, and governmental bodies will be necessary to achieve significant changes.